Development of a cost model for the production of carbon fibres. Issue 10 (October 2019) - Nunna, Srinivas; Blanchard, Patrick; Buckmaster, Derek; Davis, Sam; Naebe, Minoo
Abstract: Carbon fibre composites offer considerable potential for mass reduction in automotive applications. However, raw material cost is one of the major factors that constraints its extensive use in this mass market. Here we report a systematic study that presents the cost contributors by considering the entire process chain of the carbon fibre manufacturing. The sensitivity analysis revealed that the final cost of Polyacrylonitrile (PAN) precursor and carbon fibres were strongly influenced by tow size. It was observed that a prompt decrease in the precursor and carbon fibre cost per kg for tow sizes from 3k to 12k, later this decrement was gradual and almost became stable above 50k. Moreover, with an increase in tow size from 3k to 50k, the contribution of the precursor on the final carbon fibre cost decreased from 76.6% to 49.6%. On the other hand, the contribution of the other factors increased with increase in the tow size, for instance, labour (9.86%–17.78%), Energy (2.49%–6.48%) and Depreciation (6.11%–11.01%). Nevertheless, precursor holds the major share in determining the final price of the carbon fibres. Abstract : Chemical engineering: Mechanical engineering; Chemical reaction engineering; Chemical synthesis; Energy economics; Carbon fribre; Cost model.